Job performance of the court staff in the first district of La Union - Delfin, George O. (City of San Fernando, La Union : [s.n.], 2014)
The study assessed the job performance of the court staff in the First District of La Union. Specifically, it looked into the following: the professional attributes of the court staff in the First District of La Union along highest educational attainment, length if service, eligibility, and relevant trainings attended; the level of job performance of the court staff in the First District of La Union along quantity of work, quality of work, habits, character and integrity, cooperation, aptitude and adaptability, punctuality and attendance, industry, reliability, initiative, job knowledge, and judgment. It also tried to determine if there is significant differences exists between the perception of the judge/ clerk of court and self-rating along the job performance of the court staff in the First District of La Union; to determine if there is significant relationship between the professional attributes and level of job performance; and the strengths and weaknesses in job performance of the court staff in the First District of La Union. Finally, a proposed and validated job performance program to improve the performance of the court staff in the First District of La Union.
Bibliography: pages 98-101.
CHED-La Union
Keywords: Court clerks